Assessment of Green Supply Chain Management Practices on Sustainable Business in Ethiopia - Lemma Tadese Boson; Zenebe Elemo; Adisu Engida; Shashi Kant (Logistic and Operation Management Research (LOMR), 2023)
Evaluating organisational performance from the perspective of green paradigms is essential as "green" issues continue to gain global attention. This study evaluated organisational performance and green supply chain practices in Ethiopian Telecom. A mixed approach was considered to meet the study's aims. Structured interview questions and a questionnaire were used as a data gathering tool. Workers of Ethiopian Telecom who held managerial positions and were either directly or indirectly in charge of the business's supply chain operations made up the study's population. 386 of the 426 given questionnaires were correctly completed and used in the study, yielding an 87% response rate. AMOS; Statistical Package for the Social Sciences (SPSS) was used to analyze, interpret, and display the data collected via questionnaire. The methods of percentage, means, standard deviation, correlation, regression, and narrative analysis were used for inferential and descriptive analysis. Regarding survey results, conducted correlation analysis revealed a statistically significant positive association between the dimensions of green supply chain management and organizational performance, except eco design and operational performance; however, the overall survey result indicates that except for investment recovery, all of the dimensions of green supply chain management, including organizational commitment, eco-design, green purchasing. According to the SEM regression's findings, organizational dedication, eco-design, green purchases, and environmental practices all statistically influence how well an organization performs.